Nitro compounds as the core structures of promising energetic materials and versatile reagents for organic synthesis. (January 2020) - Zlotin, Sergei G.; Dalinger, Igor L.; Makhova, Nina N.; Tartakovsky, Vladimir A.
Abstract : This review addresses some promising areas of chemistry of nitro compounds extensively developed in recent years in Russia (particularly at the N.D.Zelinsky Institute of Organic Chemistry, Russian Academy of Sciences) and worldwide. The most important results in the synthesis of novel energetic N -, C - and O -nitro compounds are summarized. New environmentally friendly approaches to the preparation of known compounds of this series, used as components of energetic compositions, are considered. Methods for selective transformations of various nitro compounds to valuable products of organic synthesis, primarily biologically active products and their precursors, are systematically analyzed. The bibliography includes 446 references.